Slave-dealing and Slave-holding by Kutchees in Zanzibar - Aitchison, Charles Umpherston; Churchill, Henry Adrian; Shortt, Alexander Young (India Office Library and Records, 1870)
This file contains a selection of correspondence, extracts and reports regarding the involvement of British subjects from the Princely State of Kutch [Cutch] in the slave trade in Zanzibar and attempts by the British Government to end this involvement. Much of the correspondence is from Britain's Political Agent in Zanzibar, Henry Adrian Churchill and Britain's Political Agent in Kutch, Major Alexander Young Shortt. This includes translated copies of correspondence between Churchill and the Sultan of Zanzibar, Seyd [Sayyid] Majid bin Said. On folio 128, the file contains a proclamation issued by the ruler of Kutch, the Maharaja Dhiraj Mirza Maha Rao Shree Praguruljee, that warns his subjects in Kutch of the penalties of being engaged in the slave trade in general and specifically in Zanzibar.
Genre: Archival file
Keywords: Esclavage – Zanzibar